New data on the Austropotamobius torrentium (Schrank, 1803) from the tributaries of the Bosna River (Annals of the Institute of Biology, 2024)
The crayfish Austropotamobius torrentium is a dominant species of the family Astacidae in the rivers of the Black Sea and Adriatic basins of Bosnia and Herzegovina. Molecular phylogenetic studies in Europe revealed the presence of eight phylogroups. No morphometric and meristic characteristics have been determined that would clearly separate them. The paper presents new data on the morphometric parameters species Austropotamobius torrentium with watercourses Presjenica, Jošanica and Crna Rijeka. This analysis is based on 22 parameters that were measured on 38 crayfish individuals, whose size was larger than 5 cm. Using Anova test, Bonfferoni test and discrimination analysis, it was determined that females differ significantly in a small number of parameters, while males showed greater morphological divergence. The great diversity of habitats of Austropotamobius torrentium in Bosnia and Herzegovina obliges the inclusion of the Dinarides region in molecular phylogenetic studies. This will result in more precise and complete data on Austropotamobius torrentium populations.